A rare encounter in nonsuspecting circumstances: First congenital visceral leishmaniasis (kala-azar) in Libya - Elarabi, Amal; Saad, Zinab; Saadawi, Walid; Aldobea, Nadia; Sagher, Fauzi (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Congenital transmission of Leishmaniasis is very rare. It occurs through blood exchange from the mother to the child during pregnancy or delivery. We report the first confirmed congenital leishmaniasis in a 4-month-old Libyan boy with prolonged jaundice and hepatosplenomegaly. This was a congenital transmission from his mother who was asymptomatic and not known to have leishmaniasis, which was confirmed after the diagnosis of the infant. Despite treatment, the infant died. The diagnostic approach is illustrated by the case report. Poor obstetric history in the mother may be related to her own undiagnosed kala azar.
Keywords: Congenital kala azar; Leishmania infantum; visceral leishmaniasis